Application of therapeutic plasma exchange in dogs with immune‐mediated thrombocytopenia. (19th June 2020) - Kopecny, Lucy; Palm, Carrie A.; Naylor, Sean; Kirby, John; Cowgill, Larry D.
Abstract: Therapeutic plasma exchange (TPE) is an emerging treatment for dogs with immune‐mediated diseases, but reports for treatment of immune‐mediated thrombocytopenia (IMT) are lacking. These case reports illustrate the application of centrifugal TPE in 4 dogs with IMT. All dogs presented with severe hemorrhage requiring ≥1 blood transfusions, were unresponsive to conventional treatment or both. Dogs were treated with 3 sequential centrifugal TPE sessions, totaling 4.0 to 4.9 total plasma volumes exchanged per dog. In 3 dogs, TPE was associated with improvement in clinical manifestations of bleeding and platelet count in combination with immunosuppressive drugs. One dog was euthanized after 3 treatments because of persistent severe thrombocytopenia and hemorrhage. Preliminary observations indicate that TPE is safe and may be a useful adjunct in the management of IMT that is severe or refractory to traditional treatment.